A chiral coordination polymer with double coaxially nested helical chains exhibiting spin-canting antiferromagnetism1. Issue 37 (7th October 2015) - Lun, Hui-Jie; Cui, Sa-Sa; Li, Hai-Jiao; Ping, Qi; Song, Hao-Han; Li, Ya-Min; Ru, Yu; Bai, Yan-Long; Xiang, Sheng-Chang
<x xml:space="preserve">Abstract</x> A chiral coordination polymer is reported, which contains rarely two types of double coaxially nested helical chains, exhibiting spin-canting antiferromagnetism.